Substitution of Hibiscus sabdariffa with Curcuma longa in the Diets of Clarias gariepinus and the Effects on the Growth, Nutrient, and Hematobiochemistry - Uchechukwu Dennis Enyidi; I. Ayogu (Department of Aquaculture, 2023)
Phytogenic feed additives are plausible alternatives to antibiotics and serve as growth promoters in aquafeed. This research aims at finding the effects of varying inclusions of natural antioxidants like hibiscus (Hibiscus sabdariffa L.) and turmeric (Curcuma longa) on the growth, hematology, and nutrient utilization of Clarias gariepinus after 60 days feeding. This research used six feeds labeled as F1- F6 that varied in the composition of Curcuma longa and Hibiscus sabdariffa. The weight (g) inclusions of C. longa and H. sabdariffa were as follows, F1 0:250, F2 50:200, F3 100:15, F4 150:100, F5 200:50 and F6 250:0. Juvenile African catfish stocked at 9 catfish per 15L aquaria per 3 replicate aquariums (27/treatment feed) were fed for 60d. The catfish fed with F1 (250g H. sabdariffa) had the best specific growth rate 5.76±0.04 % day-1, lowest feed conversion ratio 1.01±0.01, weight gain 31.65±0.13 g, and protein efficiency ratio 0.96±0.07. The growth of African catfish increased with the increasing inclusion of hibiscus supplements. Hematobiochemical parameters ALT, AST was better for catfish fed high hibiscus supplements. We noticed that hibiscus inclusion was inversely proportional to cholesterol and total triglycerides levels of fish. The deposit of adipose tissues in the catfish was higher, with increasing inclusion of hibiscus than turmeric supplement.